Comunicação, consumo e capitalismo de plataforma:uberização do trabalho na racionalidade neoliberal - Hiller, Marcos Roberto (2024)
This thesis aims to examine the precarization of labor and the phenomenon of “uberization” in contemporary society. Seeking to deepen the understanding of the interconnections between communication, consumption, and the world of work, we begin with the premise that these new work modalities present a narrative of freedom, flexibility, and financial independence. However, they represent a means of risk transfer that intensifies control and exploitation over workers. This study investigates the creation of an entrepreneurial ideal propagated through Uber’s advertising, conceived here as a communicational device that mitigates and obscures the process of labor degradation for app-based drivers. To provide a broader analytical perspective, we conducted a binational study on platform capitalism, examining this modern mode of exploitation in both Brazil and Netherlands, where Uber’s European headquarters are located. Analyzing the experiences of app-based drivers in these two contexts reveals both structural similarities and contextual differences, reflecting the economic, social, and cultural specificities of each region. While platform capitalism imposes dynamics of deterioration of labor conditions and self-exploitation in both settings, local economic and social conditions significantly shape drivers’ perceptions and experiences, resulting in variations in the intensity and awareness of precarization. In both cases, the neoliberal narrative of autonomy and entrepreneurship collapses into a work routine marked by the constant need to maximize working hours to ensure subsistence. Particularly in Brazil, a rhetoric of freedom and entrepreneurship, heavily promoted by Uber’s shrewd advertising strategies, masks forms of algorithmic control and the erosion of traditional labor rights. These transformations reconfigure the identity of app-based drivers, whom we characterize as a new social being shaped by a neoliberal rationality rooted in contemporary society. By underscoring the social relevance of academic research, this study seeks to contribute to the discourse on the precarization of app-based labor and the inequalities of the modern labor landscape.